Spatiotemporal Variability and Trend of Ozone Pollution from Satellite Data (2003- 2021) in Iraq - Hachim, Maha S.; Rajab, Jasim M.; Al-Salihi, Ali M.; Lim, Hwee San (Iraqi Journal of Science, 2024)
Ozone (O3) occurs naturally in the Earth's upper atmosphere, and at ground level is a dangerous pollutant hurts plants and lung tissue and it’s a major component of smog. The purpose of this study to analyze the time series, trend, and spatial-temporal changes of monthly Relative Humidity (RH), Outgoing Longwave Radiation (OLR), and O3 in Iraq using the Atmospheric Infrared Sounder (AIRS) ascending AIRS3STM data during 2003 - 2021. The time series over six stations (Mosul, Sulaymaniyah, Khanaqin, Rutba, Baghdad, and Basra) have been analyzed and showed similar changes and fluctuation in O3 and OLR. The results of the study obtained were: minimum (decreasing, January–December) and maximum (increasing, May–August), and the mean and standard deviation were (0.044±0.003 ppmv) for O3 and (298± 22 Wm-2) for OLR during the study period. During December to February, the highest RH values were recorded, while the lowest RH values occurred from June to August. The monthly mean and standard deviation of RH was (28.66±29.54 g/kg). Further O3 trends revealed negative results in their annual series over all stations, except for Khanaqin and Basra, which had a positive trend. The O3 concentrations were consistently connected with other meteorological variables (the O3 has a negative correlation with RH and a beneficial correlation with temperature). The O3 spatiotemporal maps showed recorded the highest values recorded in April and May over Mosul and Sulaymaniyah (0.055–0.057), and in December, at middle and southern regions (Baghdad and Basra), there were the lowest O3 value (0.033). These results were due to meteorological and geographical factors. The results showed the efficient use of AIRS data to analyze the variations and distributions of atmospheric factors over different regions. In addition, AIRS observations can be used to obtain atmospheric, climatic, and environmental scientific reports and analyses for large, regional, and global regions and for long, continuous periods.